ChemInform Abstract: Methylidynetrisphosphonates: Promising C1 Building Block for the Design of Phosphate Mimetics. Issue 46 (24th October 2013) - Romanenko, Vadim D.; Kukhar, Valery P.
Abstract Review: 53 refs.